2012
DOI: 10.1371/journal.pone.0035752
|View full text |Cite
|
Sign up to set email alerts
|

Role of H- and D- MATE-Type Transporters from Multidrug Resistant Clinical Isolates of Vibrio fluvialis in Conferring Fluoroquinolone Resistance

Abstract: BackgroundThe study seeks to understand the role of efflux pumps in multidrug resistance displayed by the clinical isolates of Vibrio fluvialis, a pathogen known to cause cholera-like diarrhoea.MethodologyTwo putative MATE family efflux pumps (H- and D-type) were PCR amplified from clinical isolates of V. fluvialis obtained from Kolkata, India, in 2006 and sequenced. Bioinformatic analysis of these proteins was done to predict protein structures. Subsequently, the genes were cloned and expressed in a drug hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 22 publications
4
23
0
Order By: Relevance
“…It was reported that the thiolate forms at the nucleophilic cysteine residues (Cys30 in the Ec DsbA numbering) are stabilized in reduced forms of Ec DsbA and Vibrio cholera DsbA ( Guddat et al, 1998 ; Mohanty et al, 2012 ). The stabilization of the thiolate forms were suggested to result from the interactions within the C XX C moitf ( Guddat et al, 1998 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the thiolate forms at the nucleophilic cysteine residues (Cys30 in the Ec DsbA numbering) are stabilized in reduced forms of Ec DsbA and Vibrio cholera DsbA ( Guddat et al, 1998 ; Mohanty et al, 2012 ). The stabilization of the thiolate forms were suggested to result from the interactions within the C XX C moitf ( Guddat et al, 1998 ).…”
Section: Resultsmentioning
confidence: 99%
“…V. parahaemolyticus was the organism in which the first MATE family transporter, NorM, was discovered by cloning in E. coli (353), and in V. cholerae, 5 members of this family were described (16), including the NorM homolog VcmA (15), which increases MICs of fluoroquinolones, ethidium bromide, acriflavine, and doxorubicin when overproduced in E. coli. Two MATE transporters from a multidrug-resistant V. fluvialis isolate provided 2-fold increases in MIC values of ciprofloxacin and norfloxacin when expressed in E. coli (354).…”
Section: Vibrio Sppmentioning
confidence: 99%
“…As reported, MATE family efflux pumps depend upon Na+/H+ gradient for transport and have three major branches: the NorM branch, a branch containing several eukaryotic proteins and a branch containing E. coli DinF (Mohanty et al, 2012). MATE protein length varies from 400 to 700 residues comprising of 12 transmembrane helices.…”
Section: Introductionmentioning
confidence: 98%
“…MATE transporters confer resistance to bacterial pathogens and cancer cells, thus causing critical reductions in the curative efficacies of antibiotics and anti-cancer drugs, respectively (Tanaka et al, 2013). An example of one such protein is NorM, of Vibrio parahaemolyticus which is a multidrug Na +-antiporter, and was found to confer resistance to dyes, fluoroquinolones and aminoglycosides (Mohanty et al, 2012;Li and Nikaido, 2004).…”
Section: Introductionmentioning
confidence: 99%